TERAPI SENI I WAYAN KARJA: Tinjauan Konsep Bermain, Mengalir dan Menjadi Bebas Melalui Lukisan - Purwita, Dewa Gede Purwita; Kusuma Putra, I Komang Wijaya (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2022)
The pandemic does not only talk about physical health issues, but also mental and psychological problems of humans through conditions that are full of anxiety and tend to be chaotic, after a pandemic there will then be a post-pandemic phase when humans rearrange their lives to become normal. The pandemic phase which tends to be long can certainly help shape mental and psychological health conditions with all forms of things that can cause anxiety which then has a negative impact on physical health. Therefore, the role of art through painting becomes important in relieving stresses that are a source of anxiety. I Wayan Karja since 2006 has started discussing art therapeutic as a way of psychological healing. This research method uses descriptive analytic method to review the concept of playing, flowing and being free in creating paintings as a way of healing as discoursed by I Wayan Karja. As a result, the application of these three keywords is able to become an alternative way for people to stabilize their emotions through the medium of art, namely painting. therapy through this art can certainly be used by anyone to overcome certain situations that make mental and psychological stress, especially during the pandemic period as well as the aftermath.